If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4ab = 4x + -5ab Reorder the terms: 4ab + 3x = 4x + -5ab Reorder the terms: 4ab + 3x = -5ab + 4x Solving 4ab + 3x = -5ab + 4x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5ab' to each side of the equation. 4ab + 5ab + 3x = -5ab + 5ab + 4x Combine like terms: 4ab + 5ab = 9ab 9ab + 3x = -5ab + 5ab + 4x Combine like terms: -5ab + 5ab = 0 9ab + 3x = 0 + 4x 9ab + 3x = 4x Add '-3x' to each side of the equation. 9ab + 3x + -3x = 4x + -3x Combine like terms: 3x + -3x = 0 9ab + 0 = 4x + -3x 9ab = 4x + -3x Combine like terms: 4x + -3x = 1x 9ab = 1x Divide each side by '9b'. a = 0.1111111111b-1x Simplifying a = 0.1111111111b-1x
| 5(2n+6)=-4(-5-2n)+3n | | 4(3x-7)=9(2x-5) | | (3/2)x-2=19 | | 12x^2-6/-4=0 | | x+35=35 | | -14-(-11)=x/11 | | 3x+10=2x+6 | | 5x-4=6x+9 | | 20+a=2a+10 | | 4y-7=2y-38 | | 2n^3-18n^2-14n=0 | | 6ds^2-28ds+16d=0 | | 3/5x-1/10x-5 | | Log(b)64=2 | | 14j+j+4j+j-18j=14 | | c^2-3*c-10= | | (5-3x)(2x-7)=0 | | 26=11.6+y | | 7p-2p=15 | | 25v=-125 | | 2w-w=11 | | 13c-3c=20 | | n-(-7)=26 | | 3(5x-5)=25.5 | | 8g-5g=18 | | 6x-2y=-36 | | 5x+23=14 | | -16=(4/3)x-8 | | (2d)/26 | | g=(2d)/26 | | -4g+g+-7= | | 28=4+6x |